2008
DOI: 10.1093/nar/gkn895
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for direct contact between the RPA3 subunit of the human replication protein A and single-stranded DNA

Abstract: Replication Protein A is a single-stranded (ss) DNA-binding protein that is highly conserved in eukaryotes and plays essential roles in many aspects of nucleic acid metabolism, including replication, recombination, DNA repair and telomere maintenance. It is a heterotrimeric complex consisting of three subunits: RPA1, RPA2 and RPA3. It possesses four DNA-binding domains (DBD), DBD-A, DBD-B and DBD-C in RPA1 and DBD-D in RPA2, and it binds ssDNA via a multistep pathway. Unlike the RPA1 and RPA2 subunits, no ssDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…Single-stranded DNA binding protein 1 (SSCBP1) is essential for the response to DNA damage, and with the help of Integrator3 protein, it controls G(2)/M checkpoint activation (Zhang et al 2009). Replication protein A3 (RPA3), like SSCBP1, is also a single-stranded DNA-binding protein and plays a central role in many aspects of nucleic acid metabolism, including DNA replication, repair, and recombination (Salas et al 2009, Mason et al 2010. Proliferating cells are challenged with maintenance of genome integrity and chromatin organization in order to avoid aberrant gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded DNA binding protein 1 (SSCBP1) is essential for the response to DNA damage, and with the help of Integrator3 protein, it controls G(2)/M checkpoint activation (Zhang et al 2009). Replication protein A3 (RPA3), like SSCBP1, is also a single-stranded DNA-binding protein and plays a central role in many aspects of nucleic acid metabolism, including DNA replication, repair, and recombination (Salas et al 2009, Mason et al 2010. Proliferating cells are challenged with maintenance of genome integrity and chromatin organization in order to avoid aberrant gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Second, an inverse relationship between telomeric G4 structural stability and hRPA binding has been established (27,33). Third, the hRPA binding mode (1:1 complexes where one RPA is bound on the DNA in an elongated mode, or 2:1 complexes where two RPA are bound on the DNA in a compact mode) depends on hRPA concentration (18,27). Fourth, cross-linking experiments showed that the RPA1 and RPA2 subunits of the hRPA directly contact the G4 sequence (27).…”
mentioning
confidence: 96%
“…RPA carries six DNA-binding domains (DBD), four of them are located in RPA1 (DBD-A, DBD-B, DBD-C and DBD-F), one is located in RPA2 (DBD-D), and one in RPA3 (DBD-E). RPA binds to unstructured, single-stranded DNA (ssDNA) through three different binding modes involving five of the six DBD domains: DBDs A, B, C, D, and E (17)(18)(19). It is now accepted that RPA binds to ssDNA in a sequential pathway with a defined polarity (20,21).…”
mentioning
confidence: 99%
See 2 more Smart Citations